2023
DOI: 10.1002/biot.202300053
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐down of CHO cell cultivation from shake flasks based on oxygen mass transfer allows application of parallelized, non‐invasive, and time‐resolved monitoring of the oxygen transfer rate in 48‐well microtiter plates

Abstract: Cultivating Chinese hamster ovary (CHO) cells in microtiter plates (MTPs) with time‐resolved monitoring of the oxygen transfer rate (OTR) is highly desirable to provide process insights at increased throughput. However, monitoring of the OTR in MTPs has not been demonstrated for CHO cells, yet. Hence, a CHO cultivation process was transferred from shake flasks to MTPs to enable monitoring of the OTR in each individual well of a 48‐well MTP. For this, the cultivation of an industrially relevant, antibody‐produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…[25] To address the limitations of HEK293 cells, culture conditions can be optimized, or alternative cell lines such as CHO can be used. [26,27] CHO cells have a lower metabolic rate and are capable of producing high-quality glycosylated proteins, making them promising platforms for biopharmaceutical manufacturing. [27] In fact, CHO cells are already used to produce FDA and EMA approved biopharmaceuticals, highlighting the promising applicability of CHO in the pharmaceutical industry [28,33] and suggesting its potential for FGF7 production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] To address the limitations of HEK293 cells, culture conditions can be optimized, or alternative cell lines such as CHO can be used. [26,27] CHO cells have a lower metabolic rate and are capable of producing high-quality glycosylated proteins, making them promising platforms for biopharmaceutical manufacturing. [27] In fact, CHO cells are already used to produce FDA and EMA approved biopharmaceuticals, highlighting the promising applicability of CHO in the pharmaceutical industry [28,33] and suggesting its potential for FGF7 production.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] CHO cells have a lower metabolic rate and are capable of producing high-quality glycosylated proteins, making them promising platforms for biopharmaceutical manufacturing. [27] In fact, CHO cells are already used to produce FDA and EMA approved biopharmaceuticals, highlighting the promising applicability of CHO in the pharmaceutical industry [28,33] and suggesting its potential for FGF7 production. However, to the best of our knowledge, no previous studies have reported on the application of CHO cells for recombinant FGF7 production.…”
Section: Introductionmentioning
confidence: 99%